Verticulture Plant Monitoring System Using Internet of Things Based on Blynk Application - Vion Age Tricahyo; Fatra Nonggala Putra; Muhammad Lutfi Ashari (Journal of Computer Engineering, Electronics and Information Technology, 2023)
The development of technology is now very rapid. One of them is the use of the internet of things in various fields. One of the applications of technology that is developing in the world including in Indonesia is in agriculture. In this field, there is a model of how to grow plants verticulturally that utilizes limited land. In agriculture, the verticulture cropping technique known as vertical cropping requires optimal soil moisture through proper watering. So an automatic monitoring process is needed to measure soil moisture, air humidity to plant temperature. In this study focused on optimizing the automatic monitoring system using the blynk application compared to ordinary monitoring. This research also encourages further exploration of the use of micro controllers and internet of things technology in agriculture.